Charakterisierung und Modellierung von instabilen Metamaterialien - Findeisen, Claudio (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2019)
Metamaterials, composed of structural building blocks, derive their effective properties from the structure, rather than from their constituent materials they are built from. By designing and analysing a mechanical unstable metamaterial, the potentials given by structural instabilities are investigated. Furthermore the possibilities in modelling the stability behaviour and the effective properties of such materials on the different length-scales are intensively discussed throughout this work.